CDX1 improves nicotine induced cardiac fibroblasts activation and cardiomyocyte hypertrophy by alleviating autophagic flux impairment through modulation of LAPTM4B - Yue-yan Li; Fan-liang Meng; Si-yuan Zhou; Jia-min Du; Wen-jing Li; Qi-yun Liu; Lei Wu; Meng-meng Zhao; Yi Jin; Qun-ye Zhang; Ying Li; Guo-hai Su (Scientific Reports)
Abstract Nicotine-induced impairment of autophagic flux promotes the onset of myocardial remodelling, thereby exacerbating heart failure. In this study, we investigated the role and molecular mechanisms of the transcription factor CDX1 in cardiac fibroblasts (CFs) activation and cardiomyocyte hypertrophy induced by nicotine. We found that CDX1 expression was increased in response to nicotine. However, a decrease in CDX1 further exacerbated the nicotine-induced blockade of autophagic flux, thereby aggravating CFs activation and cardiomyocyte hypertrophy. This effect was attributed to the suppression of the autophagic regulator LAPTM4B transcription by CDX1 and the subsequent activation of the mTOR pathway. In contrast, CDX1 overexpression promoted LAPTM4B expression, resulting in the opposite effect. In conclusion, our study demonstrated that CDX1/LAPTM4B axis could alleviate nicotine-induced autophagy flux impairment by inhibiting mTORC1 pathway activation, thereby alleviating CFs activation and cardiomyocyte hypertrophy, and exerting cardioprotective functions.